Jejunal perfusion of simple and conjugated folates in celiac sprue - Halsted, C H; Reisenauer, A M; Romero, J J; Cantor, D S; Ruebner, B (The Journal of clinical investigation, 1977)
The intestinal absorption of [3H]-pteroylmonoglutamate (simple folic acid) and pteroyl-micron[14C]glutamyl-gamma-hexaglutamate ([14C]PG-7, conjugated folic acid) was assessed by the method of jejunal perfusion in five patients with proven celiac sprue who were studied after a gluten-containing or a gluten-free diet, and in nine normal subjects. The luminal disappearance of each folate was markedly impaired after exposure of the patients to dietary gluten and improved by gluten restriction, but not to within the range found in the normal subjects. The luminal disappearance of each folate was markedly impaired after exposure of the patients to dietary gluten and improved by gluten restriction, but not to within the range found in the normal subjects. In each experiment, column chromatography of the luminal aspirates revealed similar spectra of hydrolytic products of [14C]PG-7, whereas the fraction of the distal aspirate chromatogram appearing as pteroyl-micron[14C]glutamyl-gamma-monoglutamate ([14C]-PG-1) was similar in all three groups. By accounting for the variable effects of absorption on the luminal appearance of [14C]PG-1 and by correcting for mucosal hydrolysis which was not followed by release of [14C]PG-1 to the luminal contents, the calculated rate of in vivo hydrolysis of [14C]PG-7 to [14C]PG-1 was found impaired in both celiac sprue groups, with significant improvement on treatment. In mucosal biopsies from the sprue patients, the in vitro activity of folate conjugase in whole homogenates was higher and the activity of disaccharidase lower than in a group of 12 normal mucosal biopsies. These in vitro data suggest that the predominant cellular location of mucosal folate conjugase is different from that of disaccharidase, whereas comparison with the results of in vivo hydrolysis suggests that measurement of the enzyme in whole mucosal homogenates overestimates its significant digestive activity. The present studies indicate that (a) the mucosal lesion of celiac sprue significantly limits the intestinal absorption of both simple and conjugated folate, and (b) malabsorption of conjugated folate results from a combination of impaired hydrolysis and decreased mucosal uptake of hydrolytic product.